ANALISIS PENERAPAN PRINSIP GOOD GOVERNMENT GOVERNANCE DALAM PENGELOLAAN KEUANGAN DESA DI DESA POTO KECAMATAN MOYO HILIR - Razi Apriansyah Mustaram; Nining Sudiyarti; Zuhra Kumala (Jurnal Ekonomi & Bisnis, 2020)
The purpose of this study was to know the implementation of the principles of good government in village financial management in Poto Village, Moyo Hilir District in 2019. Type of this study was descriptive research. The data used was qualitative obtained directly from the source through interviews and observation. The informants in this study consisted of the government and some community leaders. The sampling technique used was purposive sampling. Technique to analysis data was used qualitative Miles and Huberman which consisted of data collection, data presentation and drawing conclusions. The results of study showed that of 9 principles of good government governance, there were 5 principles that had been applied, namely the principle of law enforcement, care to community, oriented towards consensus, effective and efficient and fairness. Meanwhile, 4 other principles had been implemented but not yet fully, including the principles of community participation, transparency, responsibility and accountability. The results of the discussion showed that not all principles of good government governance can be implemented in village financial management in the Poto Village government, Moyo Hilir Sub-District.